1985
DOI: 10.1007/bf00199226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a thymic factor, thymostimulin, on growth and pulmonary metastases of Lewis lung carcinoma

Abstract: The antitumor and antimetastatic activities of a thymic factor, thymostimulin (TP-1), with or without cyclophosphamide (CPA) were examined in C57BL/6 mice inoculated with Lewis lung carcinoma (3LL). Tumor growth was followed by determining the tumor diameter after tumor implantation. TP-1 given to mice every 2 days after tumor implantation significantly inhibited tumor growth without affecting the survival rate. For induction of spontaneous pulmonary metastases, 3LL cells were implanted into the footpads of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A suspension of 10 6 Preparation of effector cells. Spleen cells were harvested aseptically and gently crushed in RPMI 1640 with the flat end of a sterile syringe as described previously [31]. The cells were filtered through stainless-steel mesh and briefly rinsed in distilled water to lyze erythrocytes.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…A suspension of 10 6 Preparation of effector cells. Spleen cells were harvested aseptically and gently crushed in RPMI 1640 with the flat end of a sterile syringe as described previously [31]. The cells were filtered through stainless-steel mesh and briefly rinsed in distilled water to lyze erythrocytes.…”
Section: Animalsmentioning
confidence: 99%
“…Mice bearing spontaneous pulmonary and lymph node metastases of Lewis lung carcinoma (3LL) cells were used [16,31]. To produce spontaneous metastases, 1 × l06 viable 3LL tumor cells in 0.05 ml RPMI 1640 were injected s.c. into one hind footpad of each mouse.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Administering thymostimulin 10 mg/kg in combination with cyclophosphamide 50 mg/kg significantly prolonged the survival rate of mice with pulmonary metastases.l 24 ] In vitro assay indicated that the cytolytic activity of spleen cells against tumour cells was enhanced in mice treated with thymostimulin and/or cyclophosphamide. [24] Administering thymostimulin 10 mg/kg in combination with cyclophosphamide 50 mg/kg significantly prolonged the survival rate of mice with pulmonary metastases.l 24 ] In vitro assay indicated that the cytolytic activity of spleen cells against tumour cells was enhanced in mice treated with thymostimulin and/or cyclophosphamide.…”
Section: In Vivo Studiesmentioning
confidence: 99%